PERCEPTION OF CLIMATE CHANGE EFFECTS AMONG MAIZE AND POTATO BASED FARMERS IN CENTRAL ZONE OF PLATEAU STATE, NIGERIA - Buhari, A.; Sani, R. M.; Garba, M.; Dabo, N. M.; Abubakar, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing awareness of climate change effect on maize and potato production in Kanam and Mangu LGAs of Plateau State, Nigeria. Multistage sampling technique was employed in selecting 220 respondents. Primary data were obtained through the administration of structured questionnaire and analyzed using both descriptive and inferential statistics. The result revealed that majority (70.0) of the respondents were in their active age group with a mean of 37 years. Majority (75.5%) of the respondents were male, engaged in multiple occupations, including farming (27.3%), civil servant (41.8%), and trading (14.1%). The results also showed that majority (76.4%) of the respondents were married with small household sizes as indicated by the mean household size of 8 persons. The results further revealed that 30% and 47.3% had attended secondary and tertiary as level of education. Inheritance (45.9%) was the primary mode of land acquisition. In addition, the result also showed that sex, occupation, membership of association, access to extension, agrochemical usage and type of labour were significant (P<0.01) factors influencing farmers awareness of climate change effects on maize and potato production. Drought (92.3%), low literacy levels (89.5%), and poverty (67.3%) were identified as the major constraints to climate change mitigation strategies and were ranked 1st, 2nd and 3rd respectively. The study concluded that age, sex, membership of association, access to extension, agrochemical usage and type of labour were the factors influencing respondents’ awareness to climate change effect on maize and potato production. Based on the findings of the study the following recommendations were made; enhance the capacity of extension agents to provide timely and relevant information on climate-smart agriculture practices, encourage the adoption of climate-resilient agricultural technologies, such as drought-tolerant crop varieties, efficient irrigation systems.